Challenges associated with the treatment of Buruli ulcer - Aboagye, S.Y.; Kpeli, G.; Tuffour, J.; Yeboah-Manu, D. (Journal of Leukocyte Biology, 2019)
Buruli ulcer (BU), caused by Mycobacterium ulcerans (MU), is the third most important mycobacterial diseases after tuberculosis and leprosy in immunocompetent individuals. Although the mode of transmission remains an enigma, disease incidence has been strongly linked to disturbed environment and wetlands. The blunt of the diseases is recorded in West African countries along the Gulf of Guinea, and children 15 years and below account for about 48% of all cases globally. Prior to 2004, wide surgical excisions and debridement of infected necrotic tissues followed by skin grafting was the accepted definitive treatment of BU. However, introduction of antibiotic therapy, daily oral rifampicin (10 mg/kg) plus intramuscular injection of streptomycin (15 mg/kg), for 8 weeks by the WHO in 2004 has reduced surgery as an adjunct for correction of deformities and improved wound healing. An all-oral regimen is currently on clinical trial to replace the injectable. It is thought that a protective cloud of the cytotoxic toxin mycolactone kills infiltrating leucocytes leading to local immunosuppression and down-regulation of the systemic immune system. Our studies of lesions from BU patients treated with SR have demonstrated treatment-associated initiation of vigorous immune responses and the development of ectopic lymphoid tissue in the BU lesions. Despite these interventions, there are still challenges that bedevil the management of BU including paradoxical reactions, evolution of lesions after therapy, prolong viability of MU in BU lesions, and development of secondary bacterial infection. In this paper, we will mainly focus on the critical and pertinent challenges that undermine BU treatment toward effective control of BU.
Keywords: Immune-suppression; Leukocytes; Mycobacterium ulcerans; Mycolactone; Paradoxical reactions; Pathogenesis; Secondary bacteria infections